2016
DOI: 10.1111/jgh.13281
|View full text |Cite
|
Sign up to set email alerts
|

Topical steroids in eosinophilic esophagitis: Systematic review and meta‐analysis of placebo‐controlled randomized clinical trials

Abstract: Topical corticosteroids seem to be effective in inducing histological remission but may not have similar significant impact in improving clinical symptoms of EoE. Studies with large sample size are needed to uniformly validate symptom improvement in EoE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(82 citation statements)
references
References 34 publications
3
64
0
15
Order By: Relevance
“…Likewise, topical glucocorticoid therapy is effective in reducing eosinophil counts, epithelial hyperplasia, and subepithelial fibrosis [79]. Several rational, targeted therapies show promising results.…”
Section: Eoe Therapiesmentioning
confidence: 99%
“…Likewise, topical glucocorticoid therapy is effective in reducing eosinophil counts, epithelial hyperplasia, and subepithelial fibrosis [79]. Several rational, targeted therapies show promising results.…”
Section: Eoe Therapiesmentioning
confidence: 99%
“…Results of some studies showed that eosinophilia can improve without a significant change in clinical symptoms. 26,32,33 …”
Section: Discussionmentioning
confidence: 99%
“…Early prospective trials of fluticasone with a small number of patients by Arora et al, and Remedios et al, showed universal improvement in symptoms [95,96]. Later studies appear to contradict these impressive results.…”
Section: Topical Glucocorticoidsmentioning
confidence: 98%